Rejected Bodies: Confronting Normative Narratives in Mahesh Dattani’s Tara - Gatea, Alhawraa; Al Ghareeb, Sana (Al-Adab Journal, 2024)
Indian Playwright Mahesh Dattani has made a name for himself dealing with discriminated and neglected social groups. Born in 1958, Dattani developed a passion for theatre from a young age. He has won the esteemed Sahitya Academy Award making him one of the most prominent names in Indian literature. He has achieved international success being one of the leading figures in Indian English Theatre. Through his 1990 play Tara, Dattani treats the issues of the constriction and social discrimination associated with disability. Through this paper, disability will be dissected in light of Michel Foucault’s theories of power and normalization. The paper will highlight the resulting identity crisis associated with the disabled failure to fit into a social role and the social system’s failure towards disabled individuals. The study will also discuss the effects of the media on the dehumanization felt by the disabled. It uncovers the media’s contribution to the public’s dehumanizing gaze of curiosity; it also influences the disabled twins’ feeling of exhibitionism associated with public scrutiny. Such gaze in addition to the Foucauldian medical gaze will be judged in terms of power relations, revealing their role in further limiting the disabled agency. The study will touch upon related issues like discriminatory attitudes and stigma toward patients with disabilities and mental illness.